PENERAPAN PERMAINAN EDUKATIF MEDIA BERGAMBAR - Setiyowati, Nunuk (Thufuli, 2020)
Play is the world of children. In play there is pleasure and satisfaction without coercion oriented to the process rather than the end result. Piaget (1962), suggested that learning while playing and playing while learning is an activity that must be presented so that children have readiness to enter further education. Educative games of pictorial media have an important role in developing all aspects of children’s intelligence, because in educational play activities, pictorial games of children become active in moving and thinking so that new ideas and experiences that will be important for their growth and development will emerge. Group A children are one of the times when children have to get a lot of positive stimulation in learning to develop their full potential, imagination and intelligence aspects so that they develop optimally. At this time it is often called a critical period or a golden age that whill not be repeated again. So that the role of parent, teacher and the environment becomes the main pillar for children’s growht and development, so that children grow intro tough generations who excel and are ready to face every challenge and all the changing times.